2015
DOI: 10.1037/pag0000048
|View full text |Cite
|
Sign up to set email alerts
|

Hope for the best, prepare for the worst? Future self-views and preparation for age-related changes.

Abstract: Extending research on the impact of views on aging and developmental regulation across the life span, we tested the hypothesis that more positive views of oneself as an older person predict more preparation for age-related changes. Drawing on recent evidence regarding the domain specificity of aging-related developmental processes, we assumed this relationship to be moderated by the relevance of preparation in different life domains for different age groups. We investigated these research questions in a longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 52 publications
3
39
1
Order By: Relevance
“…Most important is the finding that the domain-specific perceived age discrimination in the domains of work, medical care, and social life were specifically predicted by views on ageing that refer to similar domains and attributes (personal competence for the work domain, physical attributes for the health care domain, and social attributes for the social domain). These results extend previous findings that domain-specific views on ageing predict behaviours and life events in related life domains (Kornadt et al 2015b).…”
Section: Domain Specificity Of the Relation Of Views On Ageing And Pesupporting
confidence: 80%
See 1 more Smart Citation
“…Most important is the finding that the domain-specific perceived age discrimination in the domains of work, medical care, and social life were specifically predicted by views on ageing that refer to similar domains and attributes (personal competence for the work domain, physical attributes for the health care domain, and social attributes for the social domain). These results extend previous findings that domain-specific views on ageing predict behaviours and life events in related life domains (Kornadt et al 2015b).…”
Section: Domain Specificity Of the Relation Of Views On Ageing And Pesupporting
confidence: 80%
“…Importantly, drawing on the previous findings that domain-specific views on ageing unfold their strongest impact in matching domains (Levy and Leifheit-Limson 2009; see also Kornadt et al 2015b), we predict similar domain-specific relations.…”
Section: Views On Ageing and Perceived Age Discriminationmentioning
confidence: 82%
“…An additional limitation is the lack of information regarding mechanisms by which SPA mediates the relationship between hopelessness and depressive symptoms. Other studies have suggested that older adults with negative SPA perceive less control, feel less productive and useful, and engage in fewer health and other activities …”
Section: Discussionmentioning
confidence: 99%
“…For example, negative SPA have been predicted by greater neuroticism, lower extraversion, and greater rigidity . Other domains of individual differences have also been found to correlate with SPA, including a measure of hope that involves perceived goal‐pursuit abilities, loss of control, level of productivity and perceived usefulness on a daily level, and preparing for the future …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation